Superoxide Generation by Nicotinamide Coenzymes - Sirota, T.V. (Biomedical Chemistry: Research and Methods, 2023)
Nicotinamide coenzymes can generate superoxide radicalsin alkaline environment. Their formation was registered by reduction of nitroblue tetrazolium (NBT) present in the buffer with formation of diformasan. Inhibition of diformazan formation occurs when superoxide dimutase (SOD) is added to the system, thus confirming generation of O₂─●. The highest superoxide generating activity was observed with NADPH. In the case of NADPH and NADH, the rate of superoxide generation was significantly lower (by approximately 50%). No O₂─● was detected when NAD was used under the same conditions and in the same time; however, 4 h later, diformasan was detected in the same sample. The superoxide generating activity decreased in the following order: NADPH > NADH ≥ NADP > NAD. Other compounds tested (adenosine, ADP and ATP) did not generate superoxide radicals even after prolonged incubation. In a cell, where a local changes in the pH of the environment are possible, nicotinamide coenzymes can be potential sources of O₂─● and thus participate in cell signaling. A change in pH can initiate this process.